Modelling of olive cake thin-layer drying process - Akgun, NA; Doymaz, I (ELSEVIER SCI LTD, 2005)
Olive cake is a sub-product of the mechanical olive oil extraction industry, which consists of pit and pulp of the olive fruit, olive oil and vegetable water. It has been using for direct combustion in bakeries and olive oil mills due to its energy content. However, the initial moisture content of olive cake is approximately 44.78% +/- 0.5 (wet basis), and this has to be reduced to about 5.% to recover its energy content. Therefore, the characterization of the thin layer drying kinetics was investigated at a wide range of drying temperatures (50-110 degrees C), a constant sample thickness and air velocity of 1.2 +/- 0.03 m/s at a laboratory scale dryer. Various mathematical models simulated drying curves of olive cake. The logarithmic model was found to give better predictions than the others. In addition, the temperature dependence of the effective diffusivity coefficient was expressed by an Arrhenius type relationship. The effective diffusivity varied between 0.3 and 1.1 x 10(-8) m(2)/s with an activation energy of 17.97kJ/mol. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: olive oil; olive cake; drying kinetics; modelling; nonlinear regression; RED-PEPPER; KINETICS; INDUSTRY; BAGASSE; PRODUCT; WASTES; Engineering; Food Science & Technology